The Eco-Environmental Changes in Typical Coastal Zones of Southern China From 1987 to 2020: A Case Study of Guangdong Coastal Counties - Li, Yuchen; Abbas, Zaheer; Chen, Danying; Zhu, Ziyang; Guo, Haijing; Zhao, Yaolong (Frontiers in Environmental Science, 2022)
Population growth, socioeconomic development, and rapid urbanization have exacerbated the deterioration of coastal ecosystems, particularly in the coastal region of southern China that has experienced significant urbanization. A precise and timely insight into the ecological changes is indicative of economic and environmental harmonization in southern coast of China and other regions of the world. This study applied 731 Landsat images to assess quantitatively the spatial and temporal evolution of ecological environment quality in the coastal zone of South China during 1987─2020 based on remote sensing ecological index (RSEI). The results show that: (1) The correlation between the RSEI calculated using Landsat data and the parameters more than 75%, and the results were significant when applied to assess the ecological environment of the coastal zone in South China. (2) The ecological quality of the coastal zone in South China as a whole showed an initial slight degradation during 1987─2020, followed by a gradual improvement trend and then a slight degradation, the area with good ecological quality decreased from 38.96% to 7.97%, and then gradually recovered to 56.61% in 2010. Subsequently, the regions with good ecological quality showed a significant decline, reducing to 1.72% and rising to 38.46% until 2020. In addition, with regional differences persisting during the study period, caused by the impact of human activities on the land use types of different landscapes. (3) Good and moderate ecological quality classes occupy most of the coastal zone in South China, but the pressure on the coastal zone is still not optimistic due to the sensitivity of the coastal zone and the accelerated urbanization in South China. As a large-scale, long time series of coastal zone ecological monitoring, this study can provide support for planning, ecological monitoring, environmental protection policy formulation and integrated regional management of coastal zones and similar areas in South China.